Informal caregivers' experiences of Covid-19 pandemic in Aotearoa : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Manawatū, New Zealand - Barnard, Tyrone (Massey University, 2023)
Informal caregivers have been reported as an understudied population and are recognised as the backbone of the health care system. The technology available today has led to increased life expectancy, and in New Zealand, 20% of caregivers are over the age of 65, which is higher than the general population. Older people are more susceptible to and at risk for the Covid-19 virus. The guidelines and rules put in place to protect the people of New Zealand from Covid-19 reduced socialisation, impacted daily activities in our lives, and created challenges for caregivers. Although caregiving is well-theorized, further research is necessary for the recent Covid-19 pandemic. This study focuses on understanding and exploring older informal caregivers' experiences of caregiving during the Covid-19 pandemic. The literature to date yields contradictory findings about how informal caregivers experienced the pandemic. Grounded theory from a constructionist perspective was used as a qualitative method in this study to explore knowledge from those who have experienced caregiving during the pandemic. Purposeful sampling was used to select participants from the Health, Work and Aged Retirement data base. This study had a sample size of 8 participants and 7 were used during data analysis. This study found the core themes of caregivers' experiences of the pandemic to be dominantly negative, and caregivers voiced the need for pre-existing supports to continue during a pandemic. The findings of this study showed caregivers experienced anxiety, felt they had a lack of information aimed at caregivers specifically and experienced a lack of support during the pandemic. These experiences are intertwined and linked, resulting in the overall negative experiences of carers. Participants asked for pre-existing supports to continue and had no suggestions outside of this as to how they can better be supported. The discussion focuses on caregivers' experiences and how they are intertwined and connected resulting in central themes. I further explore alternative ways of providing support for caregivers that meets their needs during the pandemic. It is hoped the findings of this study will contribute to the literature and support, and policies can be provided to improve caregivers' experiences in a pandemic situation.
Keywords: 520304 Health psychology